Analisis Kualitas Pelayanan dan Produk terhadap Minat Nasabah untuk Mengambil Pembiayaan Murabahah - Irfanullah, Gumilar; Desy Fitriana Sari (Journal Of Islamic Economics And Finance, 2023)
This article seeks to analyze the effect of service and product quality on customer interest in choosing Bank Btpn Syariah's low-cost financing. This research uses a type of field research with a quantitative research approach. The sample used purposive sampling technique as many as 76 samples. Data collection techniques using a questionnaire. Data analysis using multiple linear regression. The result of this study is that the service quality variable has no influence on the customer's interest in taking murabahah financing. Product variables have an influence on customers' interest in taking murabahah financing. Simultaneously, service and product quality have a significant effect on customers' interest in taking murabahah financing at BTPN Syariah. Suggestions for future researchers are expected to develop by adding interest variables.